Manifestations or seven acts and one folly - Guilherme Bandeira de Araújo, Frederico; Ferreira Praça, Heitor Levy Ferreira Praça; Schvarsberg, Gabriel; Santos, Natália Veloso (Geografares, 2014)
The theme that inspired the writing of this article was the set of street manifestations that took place in Brazil in July 2013. The manifestations were initially articulated by the problems of urban mobility, but later will acquire immense complexity. The plurality of voices and crossings and the impossibility of a single language to give existence to the complexity of the manifestations is what constitutes the raw material of this text, which causes thinking about generaliza-tions and constraints that are imposed by existing languages to talk space. The text was produced collectively or brokered by members of the Grupo de Pesquisa Modernidade e Cultura of the Instituto de Pesquisa e Planejamento Urbano e Regional, of the Universidade Federal do Rio de Janeiro and was presented as a performance in the panel discussion “In the borders of the major Geography: imagination, strangeness and performance, in the III Colóquio Internacional “A Educação pelas imagens e suas geografias”.Keywords: languages; performance; street manifestations.